Language-specific means of actualization of cognitive-pragmatic potential of evaluation - Prihodko, Ganna (Cognition, Communication, Discourse, 2025)
Evaluation covers a wide range of linguistic units across various levels of language structure, the study of which is of particular relevance at the current stage of linguistic inquiry, because the correlation and interaction of semantics and pragmatics have become one of the central issues within contemporary linguistic theory. Evaluation constitutes the essence of linguistic presentation of extralinguistic reality. Language dissects reality, restructures it, and then assigns labels to its constituent elements. Throughout the evolution of the linguistic system, evaluation—manifesting itself in explicit form—has crystallized into specific linguistic units such as affixes, lexemes, and particular syntactic constructions. The present article aims to examine language-specific mechanisms for conveying the pragma-cognitive potential of evaluative meaning. To date, the regularities underlying the emergence of evaluative vocabulary remain insufficiently investigated; particularly, the factors enabling the expression of evaluative attitudes toward referents through lexical means, as it is the word that conveys the entirety of both denotative and extradenotative content. All lexemes containing evaluative meaning can be categorized into: a) mental-evaluative, in which the evaluation comes not from the heart, but from the mind; b) emotional-evaluative, indicating feelings, usually aroused by objects that are socially appraised in a particular way. However, it must be acknowledged that a clear distinction between mental-evaluative and emotional-evaluative vocabulary is not always easily delineated, as affective expressions often incorporate an underlying cognitive appraisal. Evaluative meaning functions as a specific type of cognitive information transmitted through lexical semantics and encapsulates within the definition of a concept the cognitive framework associated with the corresponding linguistic expression. It is regarded as a macrocomponent of a word’s semantic structure, situated within the pragmatic domain and rendered explicit through interpretive mechanisms, i.e., within the realm of semantics. The diversity of evaluative meanings embedded in lexical structures reflects the multifaceted value-oriented perception of reality, as well as the complex interplay between evaluative and affective dimensions in the cognitive process. At the lexical level, evaluative meaning constitutes the conceptual foundation for both specific judgments and the emotions associated with them. It is best understood as a complex cognitive-pragmatic construct.